Undang-Undang Desa dan Bantuan Dana Desa: Village Law and Village Fund Assistance - Alfian, Alfian (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2021)
The village law has given hope for village communities to have a more prosperous life in terms of village funding which gets greater attention when compared to the above government units, namely sub-districts and districts. This has been encouraged since the assistance of village funds has been carried out in recent years. The research method used in this research is literature study method. The literature studies obtained were sourced from various kinds such as regulations / laws, journals, books and other documentation. The conclusion is that the village law contains hope for the village community for a more prosperous life. This is also supported by the existence of village fund assistance which comes from various aspects of village income. Currently the Government distributes funds sourced from the State Revenue and Expenditure Budget for Villages in 2021. The Government distributes Village funds, the amount can reach IDR 1.4 billion per village per year or an increase is given to 416 districts and 74,953 villages throughout Indonesia, but it is still constrained. plagued with a number of problems in use and accountability.